2017
DOI: 10.1111/1365-2664.13054
|View full text |Cite
|
Sign up to set email alerts
|

Metacommunities, metaecosystems and the environmental fate of chemical contaminants

Abstract: Although pollution is a major driver of ecosystem change, models predicting the environmental fate of contaminants suffer from critical uncertainties related to oversimplifying the dynamics of the biological compartment. It is increasingly recognized that contaminant processing is an outcome of ecosystem functioning, that ecosystem functioning is contingent on community structure and that community structure is influenced by organismal dispersal. We propose a conceptual organization of the contribution of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…Furthering our understanding of the ecological processes that govern contaminant fate and exposure is a key step toward managing risks in these linked aquatic−terrestrial food webs impacted by mining activities. 80 ■ ASSOCIATED CONTENT * sı Supporting Information The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.est.9b05907.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Furthering our understanding of the ecological processes that govern contaminant fate and exposure is a key step toward managing risks in these linked aquatic−terrestrial food webs impacted by mining activities. 80 ■ ASSOCIATED CONTENT * sı Supporting Information The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.est.9b05907.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therefore, it is assumed that if mobile organisms are able to identify either lethal or sublethal contaminant concentrations, they might avoid the continuous exposure (Cherry et al ; Gray ; Tierney ). The ability to move and escape from contaminants might determine the spatial distribution of organisms and the migration behavior (Gray ; Åtland and Barlaup ; Hansen et al ) and, consequently, affect the ecosystem's dynamics and functioning (Hidaka and Tatsukawa ; Schiesari et al ). For instance, behavior related to movement patterns has been used with Daphnia magna as an early warning of environmental disturbance by online biomonitoring (Ren et al ; Cano et al ; Parolini et al ).…”
Section: Spatial Avoidance and Habitat Preference Versus Behavioral Ementioning
confidence: 99%
“…The absence of attractive areas or even the absence of connectivity between ecosystems could lead to a mandatory and continuous exposure to contaminants. Because many aquatic ecosystems/habitats are connected, ecotoxicological studies should also complementarily focus on integrated ecosystem assessment rather than local ecosystems alone (Schiesari et al ). Despite the limited spatial scale of laboratory simulations, connectivity has been tested by simulating the chemical fragmentation of a habitat in a nonforced exposure system (Araújo et al ).…”
Section: Integrating Ecological Concepts To Improve Erasmentioning
confidence: 99%
“…This study examines the fate of pharmaceutical contaminants within the aquatic biota as well as the inferred transfer of contaminants from emerging adult insects to riparian predators, thus employing a meta-community approach that is uncommon in the field of ecotoxicology 17 . Recent laboratory and field studies demonstrate that a diversity of pharmaceuticals can be found in aquatic animals and riparian consumers in water bodies receiving wastewater effluents 18 , but each of these studies focused on a limited number of species and chemicals 19 21 .…”
Section: Introductionmentioning
confidence: 99%